Moisture Profile of Two Veneer Thickness Following Microwave Heat Gun Drying - Wahyudi Wahyudi (Masyarakat Peneliti Kayu Indonesia, 2006)
Application of microwave technology on the wood industries, mainly wood drying begun shortly after World War II. Full application of microwave technology at production line of wood drying industries is still being adopted in limited scales. This is due to insufficient knowledge or lack of understanding of how microwave dries wood, it consumes huge of electricity, and needs an intensive capital investment. However, several researchers have begun to conclude that employing microwave technology on wood drying will provide faster drying time, higher in rate of drying and uniformity in moisture content profiles of dried wood and no air pollution. This research is designed to investigate the application of microwave technology for drying of wood veneer in comparison to conventional drying. Drying attributes consist of moisture profiles of dried veneer, drying time, rate of drying and microwave energy consumption, using two veneer thickness of Radiata pine. The results indicated that microwave technology provides faster drying and results in higher moisture profiles of dies veneer and rate of drying compared to conventional drying